About the retromolar pad - its particularities and role in the stability and retention of the classic complete denture - Andreea Mariana Banateanu; Alexandra-Elena Biculescu; Misu Marian Babat; Paolo Di Francesco; Ioana Ana Maria Ciorniciuc; Mona Dardouk; Teodora Mihali; Anca Iuliana Popescu (Romanian Journal of Stomatology)
Aim. This paper aims to bring back into focus the area of the retromolar pad as an important element for the support area and for achieving an effective marginal seal in case of completely edentulous mandible. Material and methods. 24 cases of complete mandibular edentation were analyzed and the characteristics of the retromolar pad were followed. Analyzing the appearance of the retromolar pad, an attempt was made to classify them into the classes proposed by J. Lejoyeux. The clinical implications of various aspects of this area were monitored. Results. In patients with the retromolar pad in the last three classes, difficulties were encountered in adapting the individual tray and during the functional impression; in cases with advanced resorption of the alveolar ridge and unfavorable retromolar pad, a poor marginal seal was obtained. Conclusions. From the analyzed cases, it was reconfirmed that in an old complete mandibular edentation, the retromolar pad can take an oblique or vertical position. Such a situation becomes unfavorable for the retention of the complete denture, for the marginal seal. Knowing the particularities of the completely edentulous prosthetic field and the clinical stages is essential for maintaining denture stability.